RELEVANSI NILAI-NILAI MODERASI BERAGAMA TERHADAP KEARIFAN LOKAL DALAM DINAMIKA MASYARAKAT ISLAM DI INDONESIA: STUDI LITERATUR - Shindid Gunagraha (Academic Journal of Islamic Principles and Philosophy, 2026)
This research is based on the phenomenon of religious dynamics of the community in Indonesia which is directly adjacent to the values of local wisdom.  Local wisdom is the identity of the Indonesian nation as an archipelagic country that has social, cultural, and ethnic diversity in one framework of diversity. So that the concept of religious moderation emerged by prioritizing moderate values in multicultural and multireligious human life. Therefore, this study aims to analyze the relevance of the concept of religious moderation in the context of religious dynamics and local wisdom in Indonesia. The research method used with literature study research through a descriptive qualitative approach. The results of the study show that the values of religious moderation have relevance to various local wisdom of the Indonesian people such as mutual cooperation, deliberation, and tolerance. Culture is a form of manifestation of local wisdom both in architecture and social activities of the community so as to encourage an inclusive and tolerant Islamic society. Thus, the integration between the concept of religious moderation and local wisdom can be an effective solution in responding to various religious dynamics in Indonesia in a sustainable manner.